A comparative simulative study to determine controller schemes of static var compensator (svc) for stability of power system - Osama Butt; Muhammad Mohsin; Rasmia Irfan; Husnain Ashfaq; Kashif Habib (Mehran University Research Journal of Engineering and Technology)
A key challenge in ensuring and maintaining power system stability is the rapid management of power transients. These voltage fluctuations arise from various causes, such as sudden load changes or network faults, which, if not addressed quickly, can lead to cascading failures or even system blackouts. The Static Var Compensator (SVC) is used to mitigate the effects of power transients through the targeted use of Flexible Alternating Current Transmission System (FACTS) devices. The SVC is crucial in dynamic voltage support and reactive power compensation, making it an ideal candidate for stabilizing transient conditions. The research explores the effectiveness of various control strategies, including Proportional Integration (PI) controllers, Fuzzy Logic Controllers (FLCs), and a hybrid PI-FLC approach. The study aims to identify the most efficient scheme for enhancing SVC performance under transient conditions by comparing these control methodologies. These controllers are pivotal in modulating the SVC's reactive power output, determining how swiftly and accurately it can counteract voltage deviations. The insights gained from this investigation can inform the design of more resilient power systems that maintain stability in the face of unpredictable disturbances.